The reception of Apphia in the fourth and fifth centuries C.E. - D. F. Tolmie (Acta Theologica)
The aim of this study is to investigate the reception of Apphia (who is mentioned in Philemon 2 as one of the recipients of the letter) in the fourth and fifth centuries C.E. For this purpose the available sources are investigated in a chronological order: Jerome, John Chrysostom, Pelagius, Theodore of Mopsuestia and Theodoret of Cyrus (Apphia is not mentioned in the commentary of Ambrosiaster). Firstly, it is shown that the difference in the Biblical texts that were used by these five scholars may have had an influence on the way in which they interpreted Apphia’s role. Secondly, it is argued that one can identify a slow progression in the way in which the relationship between Philemon, Apphia and Archippus was interpreted. Lastly it is shown that personal views on women and their role had no mean influence on the perception of Apphia. For example, this can be seen in the way in which some of these authors tried to explain why Apphia was mentioned before Archippus in Paul’s letter.